IMPLEMENTATION OF LAW IN THE RESOLUTION OF DOMESTIC VIOLENCE CASES IN MEDAN: A CASE STUDY OF DECISION NUMBER 1450/PID.SUS/2025/PN MDN - Afjuni Amri Siregar; Muhammad Ridwan Lubis (Jurnal Ilmu Hukum dan Keadilan, 2026)
This study aims to analyze the process of legal implementation, the obstacles to legal enforcement, and the legal protection afforded to victims in the resolution of domestic violence cases at the Medan District Court based on Decision Number 1450/Pid.Sus/2025/PN Mdn.The results of the study indicate that the implementation of law in domestic violence cases at the Medan District Court has been carried out in accordance with the provisions of the Criminal Procedure Code and Law Number 23 of 2004 on the Elimination of Domestic Violence. Nevertheless, in practice there are still various obstacles, including limitations of evidence due to the fact that the incidents occur in the private sphere, psychological pressure experienced by victims, power relations within the household, and cultural factors that perceive domestic violence as a domestic or private matter. Legal protection for victims has been realized through judicial considerations that emphasize the safety, dignity, and rights of victims, both during the trial process and through the imposition of criminal sanctions aimed at preventing the recurrence of violence.